PERAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU GURU DI MTS NURUL FALAH TALOK KRESEK KABUPATEN TANGERANG - Malik Fatoni (Tarbawi, 2017)
This study aims to determine how the role of principal In Improving Teacher Quality in Private MTs Nurul Falah Talok Kresek Tangerang District. This research is qualitative with Field Research approach (Field Research). In this research, it is found that the head of madrasah in improving the quality of teachers in private MTs Nurul Falah Talok Kresek Tangerang Regency can be achieved. Achievement and success are based on a number of findings in the research that took place, namely 1). The Head of Madrasah has empowered the effort to improve the quality of teachers by covering various practical and logical work such as teacher competence test, guidance of teaching program and improvement of teacher professionalism, Increase of income and teacher welfare. 2). Madrasah principals undertake various development and fulfillment efforts related to infrastructure and madrasah infrastructure facilities. Another result of this research is that the success of the madrasah head that can support the process of teacher quality improvement can occur due to several factors, among others 1). Madrasah principal can play an important role as a leader with its central power to always move the artery of madrasah life, 2). The head of Madrasah is also able to understand SOP, their duties and functions for the success of madrasah accompanied by a strong attitude towards the subordinates who lead in this case the teacher in his madrasah. Keywords. Management, Human Resource Development, Madrasah.